Flood forecasting in Blue Nile basin using a process-based hydrological model - Abdel-Aziz, Osama R (International Journal of Environment, 2014)
Predictions of variations in global and regional hydrological cycles and their response to changes in climate and the environment are key problems for future human life. Therefore, basin-scale hydrological forecasts, along with predictions regarding future climate change, are needed in areas with high flood potential. This study forecasts hydrological process scenarios in Blue Nile basin using a distributed hydrological model (DHM) and predicted scenarios of precipitation from two general circulation models, CCSM3 model and Miroc3.2-hires. Firstly, river discharge was simulated by the DHM using the observed rainfall from 1976 to 1979 and then, simulating future precipitations from 2011 to 2040, discharge scenarios were predicted. DOI: http://dx.doi.org/10.3126/ije.v3i1.9938 International Journal of Environment Vol.3(1) 2014: 10-21